Implied Terms: The Foundation in Good Faith and Fair Dealing - Collins, H (Oxford University Press, 2014)
With the aim of clarifying English law of implied terms in contracts and explaining their basis in the idea of good faith in performance, it is argued first that two, but no more, types of implied terms can be distinguished (terms implied in fact and terms implied by law), though it is explained why these types are frequently confused. Second, the technique of implication of terms is distinguished in most instances from the task of interpretation of contracts. Third, it is argued that ideas of good faith and fair dealing should be acknowledged as central to the implication of terms, though different notions of good faith apply to terms implied in fact and terms implied by law. Finally, it is possible to identify a group of contracts (networks) that share an intensified economic logic of both competition and co-operation arising from their structure as a quasi-integrated production regime which require intensified duties of loyalty and co-operation implied by law.